Identification of Hub Genes in Comorbidity of Psoriasis and Vitiligo Using Bioinformatics Analysis - Wang C; Yuan J; Yu H; Lin J; Bai B (Clinical, Cosmetic and Investigational Dermatology, 2024)
Chen Wang, Jinping Yuan, Huiwen Yu, Jiaying Lin, Bingxue Bai Department of Dermatology, The Second Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of ChinaCorrespondence: Bingxue Bai, Department of Dermatology, The Second Affiliated Hospital of Harbin Medical University, Harbin, People’s Republic of China, Email baibingxue@hrbmu.edu.cnBackground: Psoriasis and vitiligo are two common autoimmune skin diseases with increased risk of comorbidities, but the common molecular mechanism about the occurrence of these two diseases is still unknown.Objective: This study aimed to identify the combined genetic profiles and evaluate the potential mechanism underlying the occurrence of this complication.Methods: The Gene Expression Omnibus (GEO) database was used to obtain the gene expression profiles of psoriasis (GSE30999) and vitiligo (GSE75819), and common differentially expressed genes (DEGs) were identified using GEO2R. DEGs were analyzed using functional enrichment analysis, protein-protein interaction (PPI) network and module construction, hub gene identification, and co-expression analysis. And hub genes were identified using Cytoscape software, and the gene expression of hub genes were validated in psoriasis (GSE13355) and vitiligo (GSE65127) datasets and immunohistochemistry at the clinical sample.Results: A total of 164 common DEGs with the same trend (137 upregulated and 27 downregulated) were selected for subsequent analysis. Functional analysis emphasized the important roles of the cell cycle and mitotic cell division, cytoskeletal reorganization, and chromatin remodeling in the complications of these two diseases. Fourteen important hub genes were identified, including BUB1, CEP55, CDK1, TOP2A, CENPF, PBK, MELK, CCNB2, MAD2L1, NUSAP1, TTK, NEK2, CDKN3, and PTTG1. Cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) may be an important immune checkpoint in the pathogenesis of the comorbidities.Conclusion: Our study identified hub genes and potential mechanisms underlying psoriasis and vitiligo complications. And we proposed a new spatio-temporal theory and the probable immune checkpoint for the pathogenesis of the comorbidity which may provide new ideas for the further research.Keywords: psoriasis, vitiligo, comorbidity, differentially expressed genes, bioinformatics, mitotic cell division, cell cycle, cytoskeleton, immune checkpoint